A dictionary of drug abuse terms and terminology - Abel, Ernest L. (Green Wood Press, 1984)
This dictionary contains words and expressions dealing with drugs of abuse along with techical terms that are frequenly encountered in this context. Many of the terms realting to marihuana have been adopted from my previous test.